(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study delves into the transformations of family, marriage, and kinship structures in contemporary societies, particularly focusing on how social, cultural, and economic factors reshape these institutions. In traditional societies, the family unit and marriage served as foundational pillars for social cohesion, with kinship networks providing support for individuals in various aspects of life. However, in the modern world, factors like globalization, urbanization, economic shifts, and changes in gender roles have altered these institutions significantly. This article investigates how these social transformations are evident in India, with specific reference to the ongoing shifts in family systems, marriage practices, and kinship structures. The paper discusses the challenges these changes bring, their social implications, and proposes solutions for adapting to new family dynamics, while still preserving valuable traditions.